Tendencies of climatic and anthropogenic changes of the marine environments in the coastal areas of Russia in the Japan Sea for the last decades - Igor D. Rostov; Natalia I. Rudykh; Vladimir I. Rostov; Alexander A. Vorontsov (Известия ТИНРО, 2016)
Complex assessment of the marine environments changes in the coastal zone of the Japan Sea at Primorye and Sakhalin coasts is presented for the last 4 decades. Both natural and anthropogenic aspects of these changes are considered with the tasks: 1) to compare interannual variability of oceanographic parameters, as water temperature, salinity, and sea level, and reveal distinctions and common tendencies; 2) to define indicators of chemical pollution and find general features of interannual dynamics for polluting substances and water quality. The data of regular oceanographic observations at 11 coastal stations and the data of pollution monitoring in certain areas conducted by hydrometeorological service of Russia (Roshydromet) in 1980-2015 are analyzed. Cyclic fluctuations with the period of 2-5 years prevail in year-to-year variability of oceanographic parameters being observed on the background of long-term trends, more significant in the 21st century. The sea surface temperature has a strong positive trend (up to 1.4o per 35 years) at many stations, with exclusion of 5 ones located in northwestern Sakhalin and central Primorye; the average trend for the whole area is 0.7о per 35 years. Majority of the stations have the significant positive trend in summer and fall, but Sovetskaya Gavan - in all seasons. For all stations, the lowest mean annual temperature was observed in 1980 and 1987, the highest one - in 1990. Salinity has a significant negative trend at all stations (up to -2.66 ‰ per 35 years), except Alexandrovsk-Sakhalinsky, with average value -1.3 ‰ per 35 years. The negative trend of salinity is more significant in spring and summer, though other tendencies could be seen locally in certain seasons. The sea level has a positive trend, significant at all stations in any season, with the maximal value in spring (on average 7 cm per 35 years that is 35-50 % of the range of seasonal fluctuations). Dynamics of pollution is described by frequency of high concentration (over the maximum permissible level) of organochlorine pesticides (HOPs), petroleum hydrocarbons (TPHs), phenols, detergents, and heavy metals. The high concentrations of TPHs and phenols are observed rather frequently, usually in the Tartar Strait and Peter the Great Bay (Golden Horn Bay, Diomid Bight, and Bosfor Vostochny Strait). In the latter area, the dangerous levels of dissolved oxygen content are observed, as well. Other pollutants don’t exceed frequently the maximum permissible level.